CORAL REEF SPATIAL DISTRIBUTION IN WANGI-WANGI ISLAND WATERS, WAKATOBI - . Yulius; Nadya Novianti; Taslim Arifin; Hadiwijaya L. Salim; Muhammad Ramdhan; Dini Purbani (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
Coral reefs contribute significant benefits in coastal area in Wangi-wangi Island, Wakatobi in terms of their ecological functions to marine biota and socio-economical services to local coastal communities. Therefore, it is importance to observe coral reef condition and its spatial distribution around Wangi-wangi island waters, Wakatobi. In this study Point Intercept Transect (PIT) and GIS tools were used to observe and analyze coral reef condition in Wangi-wangi island waters, Wakatobi. The results showed that coral reef condition in Wangi-wangi island waters can be categorized into moderate and good conditions with coverage percentage ranging from 28 – 60%. Based on spatial analysis non-acropora coral was found in greater cover percentages in Waha village, Sombu village, and Kapota island than other locations. Soft coral cover percentage was also found in larger cover percentage in Waha and Sombu regions than other locations. Keywords: coral reefs, geographic information system (GIS), Wangi-wangi Island